Analysis of the use of learning media using the participatory drawing method for elementary school children in the slum area of the Alak Landfill Kupang - Maria Theresa Dawan Mukin; Indra Y Kiling; Diana Aipipidely; Marylin Susanti Junias (Journal of Health and Behavioral Science, 2022)
Education is an important aspect of human life that is able to support future development. One of the important things in an effort to optimize a child's education at the elementary school level is to provide learning media and pay attention to the use of learning media in children's study rooms, this is so that the learning that takes place can run effectively. However, there are still learnings that have not been effective in several study rooms, one of which is the Alak Shelter House which is a study room for children who live in the slum area of ​​the Alak Landfill Kupang. This is related to the provision and use of learning media in the study room which is not yet optimal. This condition and situation certainly has a psychological effect on elementary school children who live in the slum area of ​​the Alak Landfill Kupang, especially in the learning process. This study aims to identify the use of learning media in elementary school children in the slum area of Alak Landfill Kupang and describe the psychological dynamics behind the effectiveness of the use of learning media.